Perbandingan Kata Kunci Abstrak Skripsi dengan Subjek Menggunakan Dalil ZIPF pada Skripsi Prodi Teknologi Informasi Politeknik Caltex Riau Tahun 2018 - Wahyuni, Hanis; H, Rosman; Hakim, Triono Dul (UIN Raden Intan Lampung, 2022)
This research aims to find out the comparison of keywords in thesis abstracts with subjects using zipf law in the thesis of students of IT program of Politeknik Caltex Riau 2018. The research method used in this study is a quantitative method with a comparative approach. Population and sample in this study is the entire thesis of 82 students in 2018. Based on data from the results of subjects indexing with zipf law and keywords in thesis abstracts have a relatively high level of relevance compared to relevant and irrelevant marginal. The relevant level (the resulting subject is entirely and precisely the same) of the comparison result is 79% or 65 theses, for marginal relevant (the resulting subject has similarities) of 17% or 14 theses, and for irrelevant (the resulting subject has absolutely no similarity) by 4% or three theses.